Bacteriophages safely reduce Salmonella contamination in pet food and raw pet food ingredients. Issue 3 (2nd July 2016) - Soffer, Nitzan; Abuladze, Tamar; Woolston, Joelle; Li, Manrong; Hanna, Leigh Farris; Heyse, Serena; Charbonneau, Duane; Sulakvelidze, Alexander
ABSTRACT: Contamination of pet food with Salmonella is a serious public health concern, and several disease outbreaks have recently occurred due to human exposure to Salmonella tainted pet food. The problem is especially challenging for raw pet foods (which include raw meats, seafood, fruits, and vegetables). These foods are becoming increasingly popular because of their nutritional qualities, but they are also more difficult to maintain Salmonella -free because they lack heat-treatment. Among various methods examined to improve the safety of pet foods (including raw pet food), one intriguing approach is to use bacteriophages to specifically kill Salmonella serotypes. At least 2 phage preparations (SalmoFresh® and Salmonelex™) targeting Salmonella are already FDA cleared for commercial applications to improve the safety of human foods. However, similar preparations are not yet available for pet food applications. Here, we report the results of evaluating one such preparation (SalmoLyse®) in reducing Salmonella levels in various raw pet food ingredients (chicken, tuna, turkey, cantaloupe, and lettuce). Application of SalmoLyse® in low (ca. 2–4×10 6 PFU/g) and standard (ca. 9×10 6 PFU/g) concentrations significantly ( P < 0.01) reduced (by 60–92%) Salmonella contamination in all raw foods examined compared to control treatments. When SalmoLyse®-treated (ca. 2×10 7 PFU/g) dry pet food was fed to cats and dogs, it did not trigger any deleterious side effects in the pets. Our data suggest that the bacteriophage cocktail lytic for Salmonella can significantly and safely reduce Salmonella contamination in various raw pet food ingredients.